A new and original microwave continuous reactor under high pressure for future chemistry. Issue 1 (10th October 2016) - Polaert, Isabelle; Estel, Lionel; Delmotte, Michel; Luart, Denis; Len, Christophe
Abstract : A new and original high pressure reactor has been designed and developed for continuous flow chemistry under microwaves at industrial scale. The reactor originality is that the microwave applicator is the reactor itself. It allows then the use of metallic and thick walls for the reactor adapted to a use at high pressures and high temperatures. Wave propagation coupled to heat transfer was simulated using COMSOL Multiphysics® and the design was optimized to minimize wave reflections and maximize energy transfers in the reacting medium. This leads to extremely good energy yields. Experiments confirm that the microwave energy is fully absorbed by the reacting medium. The reactor allows continuous chemical reactions at a kg/h scale, under microwave heating, up to 7 MPa and 200°C. The double dehydration of hexylene glycol has been performed under various operating conditions demonstrating then the operability of this new reactor. © 2016 American Institute of Chemical Engineers AIChE J, 63: 192–199, 2017